Evidence of validity of the Remotely-administered Visual Search Task - García, Matías Jonás (2022)
Perceptual inhibition is the executive process that contributes to selective attention by attenuating or reducing the interference effect generated as a result of distracting stimuli present in the environment. Due to the COVID-19 pandemic and other factors, it has been shown that there is a need for tools designed and validated in our environment that enable the assessment in non-face-to-face contexts. For this reason, this study aimed to provide empirical evidence of the internal validity and reliability of a Computerized Conjunction Visual Search (CVS) task. For this purpose, 97 adults aged between 30 and 35 (M = 32.21; SD 1.73; 75% females) were assessed under a remote-synchronic administration. The results obtained showed adequate reliability and validity, and the test respects the postulates of the visual search paradigm on which it is based and that its remote administration form is comfortable for users.